1999
DOI: 10.1099/00207713-49-1-51
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of rhizobia associated with Amorpha fruticosa isolated from Chinese soils and description of Mesorhizobium amorphae sp. nov.

Abstract: Fifty-five Chinese isolates from nodules of Amorpha fruticosa were characterized and compared with the type strains of the species and genera of bacteria which form nitrogen-f ixing symbioses with leguminous host plants. A polyphasic approach, which included RFLP of PCR-amplif ied 165 rRNA genes, multilocus enzyme electrophoresis (MLEE), DNA-DNA hybridization, 165 rRNA gene sequencing, electrophoretic plasmid profiles, cross-nodulation and a phenotypic study, was used in the comparative analysis. The isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(85 citation statements)
references
References 60 publications
6
76
1
1
Order By: Relevance
“…Species identification is normally based upon both genetic or genomic comparison and phenotypic characterization. Genetic distance of 0?5 in multilocus enzyme electrophoresis (Martínez-Romero et al, 1991;Wang et al, 1999), 70 % DNA-DNA relatedness in DNA hybridization Wayne et al, 1987) and 80 % similarity in numerical taxonomy (Chen et al, 1991;Gao et al, 1994) have been used or suggested as reference borders for species differentiation. These values are used in relevant analyses in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Species identification is normally based upon both genetic or genomic comparison and phenotypic characterization. Genetic distance of 0?5 in multilocus enzyme electrophoresis (Martínez-Romero et al, 1991;Wang et al, 1999), 70 % DNA-DNA relatedness in DNA hybridization Wayne et al, 1987) and 80 % similarity in numerical taxonomy (Chen et al, 1991;Gao et al, 1994) have been used or suggested as reference borders for species differentiation. These values are used in relevant analyses in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Colonies on YMA medium are circular, convex, translucent and have a diameter of 1 mm within 7-10 days at 28 u C. The generation times are 5-9 h in PY broth (Wang et al, 1999 The type strain is SDW018 T (=CCBAU 11018 T =HAMBI 2583 T ); it has the characteristics described for the species. The G+C content of the genomic DNA of the type strain is 65?1 %.…”
Section: Symbiotic Properties and Noda Gene Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the soybean symbiont Bradyrhizobium japonicum, symbiosisrelated and hydrogenase genes are localized to on a 611-kb chromosomal-borne symbiosis island that displays a distinct distribution of insertion sequence elements relative to the rest of the chromosome (Gottfert et al, 2001;Kaneko et al, 2002). Interestingly, while Mesorhizobium loti has a chromosomal-borne symbiosis island, the moderately slow-growing Mesorhizobium amorphae was found to carry a 930-kb pSym (Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several novel rhizobial taxa have been described from this region: the genus Sinorhizobium (Chen et al, 1988) and species Mesorhizobium tianshanense (Chen et al, 1995), Mesorhizobium amorphae (Wang et al, 1999), Sinorhizobium xinjiangense (Chen et al, 1988;Peng et al, 2002), Sinorhizobium kummerowiae (Wei et al, 2003), Rhizobium yanglingense (Tan et al, 2001), Rhizobium indigoferae (Wei et al, 2002) and Rhizobium loessense (Wei et al, 2003). In this paper we describe some isolates from the legume Alhagi sparsifolia, which grows wild in this region.…”
mentioning
confidence: 99%